2021
DOI: 10.1002/hep.32221
|View full text |Cite
|
Sign up to set email alerts
|

Breviscapine alleviates NASH by inhibiting TGF‐β‐activated kinase 1‐dependent signaling

Abstract: Background and Aims: NAFLD is a key component of metabolic syndrome, ranging from nonalcoholic fatty liver to NASH, and is now becoming the leading cause of cirrhosis and HCC worldwide. However, due to the complex and unclear pathophysiological mechanism, there are no specific approved agents for treating NASH. Breviscapine, a natural flavonoid prescription drug isolated from the traditional Chinese herb Erigeron breviscapus, exhibits a wide range of pharmacological properties, including effects on metabolism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Undoubtedly, treating hepatic inflammation is a valuable method to treat NASH. The research of Lan et al further confirmed the feasibility of drugs targeting inflammation in treating NASH [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, treating hepatic inflammation is a valuable method to treat NASH. The research of Lan et al further confirmed the feasibility of drugs targeting inflammation in treating NASH [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A mouse model of NASH was established by feeding a high-fat/high-cholesterol diet, for 16 weeks, and breviscapine (15 and 30 mg/kg) was administered daily by oral gavage after 8 weeks of treatment, significantly reduced lipid accumulation, inflammatory cell infiltration, liver injury, and fibrosis in mice. Further RNA-sequencing and multiomics analyses indicated that breviscapine inhibited TGF-β-activated kinase 1 (TAK1) -dependent signaling to alleviate NASH ( Lan et al, 2022 ). Moreover, in vitro and in vivo results of the experiment showed that gastrodin (25, 50, 100, 200 μg/ml; 10, 20, 50 mg/kg) activated the AMPK/Nrf2 pathway, ameliorated hepatic oxidative stress/proinflammatory response and significantly improved metabolic disorders in NAFLD ( Qu et al, 2016 ).…”
Section: Effects Of Extracts/monomers From Tcms Against Hepatic Fibrosismentioning
confidence: 99%
“…Bufalin regulated tumor immune microenvironments by Nuclear Factor kappa B (NF-κB) and activates anti-tumor T cell immune response [ 30 ]. Breviscapine alleviated nonalcoholic steatohepatitis and liver fibrosis by inhibiting TGF-β-activated kinase 1 and toll-like receptor 4 (TLR4) / NF-κB signaling pathway to protect the liver and prevent the further development of liver disease to HCC [ 31 , 32 ]. Astragaloside IV inhibited macrophage M2 polarization, invasion and proliferation of hepatocellular cells by regulating TLR4 / NF-κB / signal transducer and activator of transcription 3 (STAT3) signaling pathway [ 33 ].…”
Section: Introductionmentioning
confidence: 99%